Existence theory and Hyers-Ulam stability for a couple system of fractional differential equations - S. Kouachi (Surveys in Mathematics and its Applications, 2019)
We discuss the existence and uniqueness of solutions for a coupled system of fractional differential equations by the help of some fixed point theorems. Further, we investigate the Hyers-Ulam stability results for the proposed problem. An example is also included to illustrate the established results.